2003
DOI: 10.1159/000072293
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility, Phage Typing and Plasmid Profile of <i>Salmonella enterica</i> Serotype <i>paratyphi A</i> Strains Isolated in Kuwait

Abstract: Objective: To determine the antimicrobial susceptibility, phage type and plasmid profile pattern of Salmonella enterica serotype paratyphi A strains isolated in Kuwait. Material and Methods: From January 1995 to December 1999, 106 strains of S. enterica serotype paratyphi A isolated from an equal number of cases of enteric fever, attending the Infectious Disease and Mubarak Al-Kabeer Hospitals in Kuwait were investigated. The isolates were tested for antimicrobial susceptibility to 8 commonly used antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The probable reasons for this difference may be due to the population mix, because our hospital is a specialized hospital dealing with only infectious disease patients. Our present observation is similar to our previous reports [7][8][9] .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The probable reasons for this difference may be due to the population mix, because our hospital is a specialized hospital dealing with only infectious disease patients. Our present observation is similar to our previous reports [7][8][9] .…”
Section: Discussionsupporting
confidence: 94%
“…The percentage of MDR strains during the study period remained between 23 and 48%. Panigrahi et al [7] in an earlier study from our hospital had reported that 45% of the isolates of S. typhi between January 1993 and December 1994 were MDR but there were no MDR strains among S. paratyphi A [8] . The percentage of MDR S. typhi has decreased from 45 to 23% in 2001.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The whole genome of S. Paratyphi A strain ATCC 9150 has been sequenced (McClelland et al 2004), and there have been no reports that it harbors plasmids. Some small plasmids that are harbored in S. Paratyphi A have been continually reported, such as plasmids of 2.2, 5, and 20 kb reported in Kuwait (Panigrahi et al 2003); 2.2 and 20 kb reported in Wenzhou, China (Chu et al 2005); and 3.6 and 9.5 kb reported in Guiyang, China (Zhang et al 2004a).…”
Section: Introductionmentioning
confidence: 99%